Advokasi Kelembagaan Islam terhadap Perampasan Tanah: Analisis Komparatif atas Peran MUI, Muhammadiyah, dan NU di Indonesi - Ghazali, Abdullah; bin Abdul Rahman, Mohamad Zaidi; Bin Md Rasip, Osman; Bawana, Tate Agape (Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study examines the role of Islamic institutions in advocating against land grabbing in Indonesia, focusing on the Indonesian Ulema Council (MUI), Muhammadiyah, and Nahdlatul Ulama (NU). The objective is to analyze their motives, strategies, and effectiveness in responding to agrarian conflicts. The research adopts a qualitative case study approach, drawing on six semi-structured interviews, sixteen fatwas and official recommendations, journal articles, and policy documents. Data were analyzed through the Advocacy Coalition Framework (ACF) and interpreted thematically. Findings reveal three main drivers of institutional engagement: concern for environmental and agrarian justice, responses to human rights violations, and grassroots grievances. Advocacy strategies include public education, fatwa issuance, legal assistance in cases such as Rempang and PIK 2, and coalition-building with civil society organizations. Theoretically, the study expands ACF by incorporating the Islamic principles of maslahah (public good) and ‘adl (justice). Empirically, it provides detailed evidence of how MUI, Muhammadiyah, and NU engage in agrarian justice. Practically, the study offers insights for policymakers and civil society to strengthen collaboration between Islamic institutions and advocacy networks in addressing land grabbing.